IDENTIFIKASI JENIS BAKTERI PADA RUMPUT LAUT Eucheuma cottonii YANG TERSERANG ICE-ICE - Rosalia Adedelcy Fernandez; Yuliana Salosso; Immaria Fransira (Jurnal Aquatik, 2026)
Ice-ice disease is one of the main obstacles in the cultivation of Eucheuma cottonii seaweed which can reduce the growth, quality, and carrageenan content. This study aims to identify the types of bacteria found in E. cottonii seaweed infected with ice-ice disease and determine its effect on carrageenan levels. The study was conducted in August–October 2025 with samples taken at Pasir Panjang Beach, Kupang City. Bacterial identification was carried out at the Fish and Environmental Health Laboratory UPT using the API 20 E method, while carrageenan analysis was carried out using the alkali extraction method. Water quality parameters measured included temperature, salinity, pH, and dissolved oxygen (DO). The results showed that the bacteria identified in the seaweed samples were Vibrio alginolyticus, while no pathogenic bacteria were found in the water samples. Healthy seaweed produced carrageenan yields of 28.0% and 32.0%, while seaweed infected with ice-ice only produced yields of 17.0% and 12.0%. Water quality measurements showed a temperature of 32.8°C, a salinity of 30 ppt, a pH of 8.1, and a DO of 7.50 ppm. The results showed that the presence of Vibrio alginolyticus is associated with ice-ice disease in E. cottonii and results in decreased carrageenan levels. Environmental conditions, particularly relatively high temperatures, are thought to increase the seaweed's susceptibility to bacterial infection. Key words: Eucheuma cottonii, ice-ice disease, Vibrio alginolyticus, carrageenan, water quality.